2017
DOI: 10.1186/s41100-017-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Causative organisms and outcomes of peritoneal dialysis-related peritonitis in Sarawak General Hospital, Kuching, Malaysia: a 3-year analysis

Abstract: Background: Peritoneal dialysis peritonitis remains a significant cause of morbidity for peritoneal dialysis patients and the main reason for conversion from peritoneal dialysis to hemodialysis. As the characteristics of patients and microbial susceptibility vary from center to center, the aim of this study is to evaluate the microbiology and the clinical outcomes among continuous ambulatory peritoneal dialysis patients in Kuching, Malaysia. Methods: This is a retrospective record review of 82 continuous ambul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(22 reference statements)
2
2
0
1
Order By: Relevance
“…In our setting, CNP accounted for 28.2% of the overall peritonitis cases, which was similarly reported in another center in Malaysia (28.2%)[ 12 ] and in the United Kingdom (>20%). [ 17 ] Whereas the other centers reported a lower incidence of CNP rates (<15%).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our setting, CNP accounted for 28.2% of the overall peritonitis cases, which was similarly reported in another center in Malaysia (28.2%)[ 12 ] and in the United Kingdom (>20%). [ 17 ] Whereas the other centers reported a lower incidence of CNP rates (<15%).…”
Section: Discussionsupporting
confidence: 83%
“…[ 2 11 ] Our prominent initial empiric combination (ceftazidime/cefazolin) was also reported to be the initial empirical antibiotic of choice in another center in Malaysia. [ 12 ] Both achieved a resolution rate of more than 70%. On the contrary, studies in other countries had reported the use of an aminoglycoside with vancomycin or cefazolin as their first-line initial empirical antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Most cases of PD-related peritonitis are due to gram-positive organisms, though there is a growing body of evidence to suggest that gram-negative infections are increasing in countries like China and Malaysia. 4,5 Upon review of our home dialysis program's causative organisms for peritonitis, we found that our peritonitis rates were consistent with other developed countries (see Figure 1 and Table 2).…”
Section: Discussionsupporting
confidence: 80%
“…Another retrospective study in Sarawak, Malaysia, reported similar occurrence of gram-negative and gram-positive organisms causing peritonitis, with trend of increasing gram-negative infection with time, causing higher rate of catheter loss. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%